Development of an Agro-Food complex on the basis of economic integration - Rohoza, Mykola; Perebyynis, Vasyl; Havrysh, Valerii; Verhal, Kseniia; Perebyynis, Yuliya (Research Papers in Economics and Finance, 2019)
The agro-food complex combines agriculture, food-processing industry and agricultural trade. It has been established that integration is an effective tool for formation and functioning of this complex. However, due to the unstable political and economic situation in recent years, there is a decrease in production of certain types of food in Ukraine. A vertically integrated structure which looks like a two-tier hierarchical structure has been studied. The purpose of its functioning is profit maximization at the expense of the synergetic effect, resource saving, etc. Under strict vertical integration, profit distribution can be made on the basis of distribution mechanisms of scarce resources, using priorities where expenses of enterprises can be considered a priority. The problem of formation of an effective vertically integrated structure can be brought to solving the issue of the smallest covering of a set. It has been proved that a boundary value of an index of vertical integration is determined by a share of energy resources in the process of production and the potential of their production. In Ukraine, the use of biogas complexes can provide growth of the mentioned index to 0.25. This corresponds to the ratio of energy resources in the crop production cost structure.